2019
DOI: 10.1186/s12879-019-3671-6
|View full text |Cite
|
Sign up to set email alerts
|

Identfication of viral and bacterial etiologic agents of the pertussis-like syndrome in children under 5 years old hospitalized

Abstract: BackgroundAcute respiratory infections (ARIs) represent an important cause of morbidity and mortality in children, remaining a major public health concern, especially affecting children under 5 years old from low-income countries. Unfortunately, information regarding their epidemiology is still limited in Peru.MethodsA secondary data analysis was performed from a previous cross-sectional study conducted in children with a probable diagnosis of Pertussis from January 2010 to July 2012. All samples were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
12
1
2
Order By: Relevance
“…However, in clinical practice, we found that other pathogens can also cause pertussis-like cough as part of pertussis-like syndrome. Stephanie Saiki-Macedo found that in Peru, there was a high prevalence of ADV, B. pertussis, MP and IV-B infection in patients with a probable diagnosis of pertussis [10]. In our study, detailed etiological examination was performed in 281 children who had typical pertussis-like syndrome.…”
Section: Discussionmentioning
confidence: 82%
“…However, in clinical practice, we found that other pathogens can also cause pertussis-like cough as part of pertussis-like syndrome. Stephanie Saiki-Macedo found that in Peru, there was a high prevalence of ADV, B. pertussis, MP and IV-B infection in patients with a probable diagnosis of pertussis [10]. In our study, detailed etiological examination was performed in 281 children who had typical pertussis-like syndrome.…”
Section: Discussionmentioning
confidence: 82%
“…The differentiation of pertussis and respiratory infections with pertussis-like coughing is possible only by determining causative microorganisms. B. parapertussis, Mycoplasma pneumoniae, Chlamydia pneumoniae, RSV, influenza virus, parainfluenza virus, adenovirus, metapneumovirus, rhinovirus and bokavirus are other microorganisms which should be considered in the differential diagnosis of pertussis [4,[20][21][22][23]. In our study, influenza virus, RSV, rhinovirus, parainfluenza virus, adenovirus, bocavirus and parainfluenza were causative agents in patients in Group 3.…”
Section: Discussionmentioning
confidence: 65%
“…Although it is vaccine preventable disease, it is endemic among children all over the world almost all the time and leads to outbreaks from time to time [2][3]. Other than B. pertussis there are respiratory tract infections which cause pertussis like coughing [4]. Clinical picture is difficult to differentiate between these entities.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoudi et al (3) found that RSV was the most frequently detected pathogen (20%), followed by adenovirus (16%), PIV (11%), and metapneumovirus (10%). Saiki-Macedo et al (4) performed a retrospective analysis of the etiology of pertussis-like syndrome in 288 children under 5 years old. The most frequently isolated pathogen was adenovirus (49%), followed by M. pneumoniae (26%) and influenza B virus (19.8%).…”
Section: Discussionmentioning
confidence: 99%